(untitled) (Academia Science Repository, 2023)
This study explores the use of linguacultural analysis as a tool for understanding the representation and verbalization of cultural concepts in texts. The study begins by defining linguacultural analysis and its key elements, including the examination of the language used in texts and the cultural context in which they were produced. The study then provides a comprehensive overview of previous research in the field of linguacultural analysis, including the methods and techniques used in previous studies and the key findings that have emerged from these studies. The study also includes a case study that applies linguacultural analysis to a text produced in a specific cultural context. This case study demonstrates the usefulness of linguacultural analysis for understanding the ways in which cultural concepts are constructed and conveyed in texts, and for exploring the relationship between language and culture. Overall, this study highlights the importance of linguacultural analysis for understanding the representation and verbalization of cultural concepts in texts, and for exploring the complex relationships between language and culture.